DAMPAK PENTUPLE BOTTOM LINE TERHADAP NILAI PERUSAHAAN (STUDI PADA SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Ayu Febryanti, Elisa; Dewi N.O, Chyntia; Alya, Qhuluqi; Yovita R. Pandin, Maria (Jurnal Ilmu Akuntansi, 2023)
This study aims to analyze the impact of the pentuple bottom line influence on company value in the pharmaceutical sector listed on the Indonesia Stock Exchange (BEI). The pentuple bottom line approach refers to a framework that evaluates company performance based on five main factors: Profit, People, Planet, Phenotechnology, and Prophet. Descriptive quantitative research method with secondary data from company sustainability reports was used. The study population consisted of pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2022. The sampling technique used was purposive sampling. Data analysis in this study used the software SPSS version 22 as a tool. Data techniques used in this research included descriptive statistical tests, classical assumption tests, and hypothesis testing, including multiple linear regression analysis, coefficient of determination (R2) test, T-test, and F-test used to examine the relationship between the pentuple bottom line approach and company value in the pharmaceutical industry on the Indonesia Stock Exchange. This study is expected to provide insights into the importance of implementing sustainable business practices and social responsibility in enhancing company value.